Analiza javnega financiranja športa v Republiki Sloveniji z vidika glavnih virov financiranja - Čater, Tomaž (Šport (Ljubljana), 2016)
Because sport is a mixed (public and private) good it makes sense to be financed also with public funds. Most public funding of sport in Slovenia is associated with the local communities, followed by state and EU funds, while a smaller share is contributed by the Foundation for Sport. Public funds for sports over the last 15 years have increased much in nominal terms. However, if we remove the effect of inflation and adapt the numbers to a constant level of GDP, the increase of public funds for sports is much smaller. Virtually all types of public funding for sport is closely related to the economic situation in the country which means that the funds for sports increase/decrease when the GDP and the state and local budgets increase/decrease.
Keywords: finance; financiranje; javni viri; javno financiranje; public financing; public sources; Slovenia; Slovenija; sport; šport